Strategi Komunikasi Pemasaran Kae Thai Tea Dalam Meningkatkan Brand Awareness - Noti, Fetnisari Babang; Widodo, Herru Prasetya; Setiamandani, Emei Dwinanarhati (Jurnal Komunikasi Nusantara, 2021)
The current business competition is so tight that there are many similar competitors. This is where a brand awareness strategy is needed so that the business being run can still compete. This study aims to determine the strategies used by Kae Thai Tea in increasing this brand awareness. In this study, a qualitative research method was used through observation, documentation and semi-structured interviews with informants who were determined through positive sampling. From the research carried out, it can be concluded that in carrying out a marketing communication strategy to increase brand awareness, this goal can be achieved by implementing a well-organized strategy in accordance with the wishes of the businessman. As for several supporting factors, namely the elements of marketing communication and brand elements by having a concept that is quite affordable. The presence of several inhibiting factors will not make the marketed brand worse but will become stronger in the face of competition. Keywords: communication; marketing communication; brand awareness